Isokinetic concentric versus eccentric training of shoulder rotators with functional evaluation of performance enhancement in elite tennis players - Mont, M. A.; Cohen, D. B.; Campbell, K. R.; Gravare, K.; Mathur, S. K. (The American Journal of Sports Medicine, 1994)
Thirty elite tennis players were randomly assigned to three groups to evaluate shoulder isokinetic internal and external rotation training: an isokinetic concentric group, an isokinetic eccentric group, and a control group with no training. Subjects were tested before and after training both concentrically and eccentrically using an isokinetic dynamometer. Functional output before and after training was assessed by the average and peak velocity of six maximal serves. The effect of training on serve velocity endurance was also assessed. Statistically significant concentric and eccentric strength gains (11%) were obtained in both training groups when compared with controls (decreased total average strain of 2%) (P < 0.0004). Serve velocity increased by greater than 11% in both training groups, which was a significant increase from the average of 1% in the control group (P < 0.0001). In the endurance study, training group subjects displayed a tendency to maintain their serve velocity (loss of approximately 2%) greater than controls (loss of 6.4%) (P < 0.05). Isokinetic training led to increases in objective and functional output in elite tennis players. This training regimen may have significance in the final stages of the rehabilitation of injured shoulders as well as in improved performance and reduced injury risk.